Inhibition of cholesterol transport impairs Cav‐1 trafficking and small extracellular vesicles secretion, promoting amphisome formation in melanoma cells. (6th January 2023) - Peruzzu, Daniela; Boussadia, Zaira; Fratini, Federica; Spadaro, Francesca; Bertuccini, Lucia; Sanchez, Massimo; Carollo, Maria; Matarrese, Paola; Falchi, Mario; Iosi, Francesca; Raggi, Carla; Parolini, Isabella; et al.
Abstract: Caveolin‐1 (Cav‐1) is a fundamental constituent of caveolae, whose functionality and structure are strictly dependent on cholesterol. In this work the U18666A inhibitor was used to study the role of cholesterol transport in the endosomal degradative‐secretory system in a metastatic human melanoma cell line (WM266‐4). We found that U18666A induces a shift of Cav‐1 from the plasma membrane to the endolysosomal compartment, which is involved, through Multi Vesicular Bodies (MVBs), in the formation and release of small extracellular vesicles (sEVs). Moreover, this inhibitor induces an increase in the production of sEVs with chemical–physical characteristics similar to control sEVs but with a different protein composition (lower expression of Cav‐1 and increase of LC3II) and reduced transfer capacity on target cells. Furthermore, we determined that U18666A affects mitochondrial function and also cancer cell aggressive features, such as migration and invasion. Taken together, these results indicate that the blockage of cholesterol transport, determining the internalization of Cav‐1, may modify sEVs secretory pathways through an increased fusion between autophagosomes and MVBs to form amphisome, which in turn fuses with the plasma membrane releasing a heterogeneous population of sEVs to maintain homeostasis and ensure correct cellular functionality. Abstract : The model describes the role of cholesterol transport in sEVs secretion. CTR: Cav‐1 is present in PM to form functional caveolar structures; it is involved in the formation of MVBs and included in secreted exosomes (autophagic process is inhibited). U18666a determines Cav‐1 internalization within endolysosomal compartments (autophagic process is activated) resulting in the alteration of the classical mechanism of sEVs biogenesis. Autophagosomes fuse with MVBs and lead to the production of amphisomes that fuse with PM to release heterogeneous sEVs.